2014
DOI: 10.1002/hed.23534
|View full text |Cite
|
Sign up to set email alerts
|

Maximum mouth opening and trismus in 143 patients treated for oral cancer: A 1‐year prospective study

Abstract: Postoperative radiotherapy and maxillary or mandibular tumor involvement are the highest contributing risk factors to decreasing MMO and the subsequent development of trismus after oral cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
123
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(142 citation statements)
references
References 38 publications
12
123
7
Order By: Relevance
“…At the end of radiotherapy, a reduction of the MMO was observed in all study patients, as it was reported by others, too [12]. Trismus was observed in 3 of 8 patients (37.5%), while the mean MMO in all patients was below the limit of trismus.…”
Section: Discussion Trismussupporting
confidence: 86%
See 3 more Smart Citations
“…At the end of radiotherapy, a reduction of the MMO was observed in all study patients, as it was reported by others, too [12]. Trismus was observed in 3 of 8 patients (37.5%), while the mean MMO in all patients was below the limit of trismus.…”
Section: Discussion Trismussupporting
confidence: 86%
“…The absence of specific criteria for the definition of trismus and the non-homogeneous group of patients in the different studies are also some of the main reasons for the above wide variation of the prevalence of trismus in head and neck cancer patients [6,9,12,13].…”
Section: Discussion Trismusmentioning
confidence: 99%
See 2 more Smart Citations
“…As found in other studies, the mean age of the sample was over 60 years 5,[8][9][10] , the dominant sex is male and the location most affected by tumors is the tongue 5,[7][8] .…”
Section: Discussionmentioning
confidence: 51%